Effect of extraction temperature on composition, structure and functional properties of flaxseed gum. (15th January 2017) - Kaushik, Pratibha; Dowling, Kim; Adhikari, Raju; Barrow, Colin J.; Adhikari, Benu
Highlights: Temperature selective extraction of FG for specific applications is proposed. The monosaccharide content of FG decreased with the rise in extraction temperature. NMR analysis confirmed the absence of galacturonic acid in all the FG samples. The EAI of FG is strongly influenced by content and form of protein present. Oil absorption capacity of FG increases with the rise in extraction temperature. Abstract: Flaxseed gum (FG) was extracted at four different temperatures (30, 50, 70 and 90 °C). Chemical composition and structural features of FG extracted at different temperatures were investigated to determine the effect of temperature. Content of acidic monosaccharides and denatured protein increased with increasing FG extraction temperature. The ratio of neutral to acidic monosaccharides decreased from 6.7 to 5.7 as the extraction temperature was increased from 30 to 90 °C. Physiochemical and functional properties, including zeta-potential, surface morphology, emulsifying activity index (EAI) and emulsion stability index (ESI), water absorption capacity (WAC) and fat absorption capacity (FAC) of FG samples, were also investigated as a function of extraction temperature. EAI and WAC of FG samples reduced significantly with rise in extraction temperature. Our study suggests that FG extracted at different temperatures may be specifically targeted for different applications, such as for emulsification or gel formation in food systems.